Breast Imaging: Correlation Between Axillary Lymph Nodes Apparent Diffusion Coefficient and Pathological Lymphovascular Invasion in Patients With Invasive Breast Cancer - Ahmad M. Mounir; Farah Ahmed Shokeir; Ghada H. Abd Elraouf (European Journal of Breast Health)
Objective: Together with local invasion, one of the important characteristics of cancer is its capacity to spread, resulting in metastases. Before cancer cells metastasize to a secondary site, they must first enter and spread through the blood and lymph vasculature, this is known as lymphovascular invasion (LVI). This LVI and, to a much lesser extent, perineural and neural invasion are one of the biologic prerequisites for systemic spread and metastases. To evaluate the correlation between pre-operative apparent diffusion coefficient (ADC) of the ipsilateral enlarged axillary lymph nodes (LNs) and presence of LVI on post-operative pathology, in patients with invasive breast cancer. Materials and Methods: This retrospective study was approved by the institutional review board. It included 100 female patients (mean age, 49 years; range, 30–68 years) with invasive breast cancer, who underwent preoperative magnetic resonance imaging (MRI) and breast surgery. On pre-operative MRI, the ADC was calculated for the ipsilateral enlarged axillary LN. Presence or absence of LVI was assessed on post-operative histopathology. Statistical analysis was performed to investigate any correlation between the ADC value of the axillary LNs and LVI in these patients. Results: The mean ADC value of the ipsilateral enlarged axillary LNs was significantly lower in LVI positive cases compared to LVI negative cases (0.735 × 10−3 mm2/s) vs. (1.024 × 10−3 mm2/s), (p<0.001). Moreover, the mean Ki-67 in LVI positive cases was 46.12%, compared to 21.58% for LVI negative cases. This higher Ki-67 level in LVI positive cases indicates a greater degree of proliferation and thus the more aggressive nature of these tumors, and this was positively correlated with ADC values of the ipsilateral enlarged axillary LNs. Conclusion: In cases of invasive breast cancer, the ADC value of the ipsilateral enlarged axillary LNs assessed on pre-operative MRI, and Ki-67 status of the tumor were significantly correlated to the LVI status on histopathological assessment. This ADC value may be useful as a predictor of axillary LN involvement, metastasis, and prognosis in invasive breast cancer.